Business model renewal in context of integrated solutions delivery: a network perspective - Rajakallio, Karoliina; Ristimäki, Miro; Andelin, Mia; Junnila, Seppo (International Journal of Strategic Property Management, 2017)
Successful business model renewal requires the companies to understand the changes that the new business model causes with respect to their activities, value drivers and value appropriation logic. The study employs a comparative case study strategy. Conceptualizing business models as activities, the changes that adopting an integrated solution business model to implement a real estate development causes to the business models of companies in the project delivery network, compared to their business models applied in conventional project delivery networks following a disintegrated approach, is analyzed. The findings suggest that the shift towards more integrated project delivery models causes significant changes in the alignment of value drivers and value appropriation mechanisms across the network of firms. Simultaneously, companies adhere to their existing activity content and governance. The results contradict previous studies on the organizational impact of shift towards integrated solutions. Existing research on integrated solutions and alliances has primarily focused on developing practices from the perspective of a customer - producer relationship. This study gives valuable insights related the importance of the internal logic of the service providers in achieving successful project coalition.